Organisation and Diversification of the Educational Market in Poland: The Case of the Poznań Agglomeration - Walaszek, Marzena; Bąkowska, Edyta (Quaestiones Geographicae, 2016)
The political changes in Poland after 1989 affected the formation of a self-reliant society. One of the results was the decentralisation of public tasks in the field of education, with the relevant competences transmitted to local governments. Since then, communes have been responsible for ensuring equal access to public education, but at the same time a non-public education market has been developing. Important for changes in the Polish educational system was also a reform started in 1999 which led to the transformation of the two-level system of education existing since 1968 into a three-level structure. The first non-public schools began to form as an alternative to public ones. Currently, non-public schools are mainly run by non-governmental organisations, religious institutions or social associations. In the general opinion, the quality of education in non-public schools is higher than in public ones (smaller classes, better contact between student and teacher, an individual approach to each student). In the face of education-model changes it is important to create a wide range of learning opportunities for everyone. It is also not about competition, but cooperation among all institutions involved in education provision. In this article, the progressive diversification of the educational market is presented on the example of the Poznań agglomeration.A diversified educational system, its commercialisation, and the creation of new educational opportunities for children and young people beyond the basic programme of education are undoubtedly benefits for the Polish society. The growing competition among the wide range of educational institutions (also taking into account institutions organising extra-curricular classes), from a theoretical point of view, should help to improve the quality of education in the entire market of educational services. As a consequence, these trends, together with demographic changes, may invite the question about the prospects of public schools in their present form in the future.